Ultrasonography for Injecting (Around) the Lateral Epicondyle: EURO-MUSCULUS/USPRM Perspective - Ricci, Vincenzo; Mezian, Kamal; Cocco, Giulio; Tamborrini, Giorgio; Fari, Giacomo; Zunica, Fiammetta; Chang, Ke-Vin; Kara, Murat; Özçakar, Levent (Diagnostics (Basel, Switzerland), 2023)
Lateral epicondylitis (LE) is a very common and painful condition seen in the daily practice of musculoskeletal physicians. Ultrasound-guided (USG) injections are commonly performed to manage the pain, promote the healing phase, and plan a tailored rehabilitation treatment. In this aspect, several techniques were described to target specific pain generators i the lateral elbow. Likewise, the aim of this manuscript was to extensively review those USG techniques together with the patients' pertinent clinical/sonographic features. The authors believe that this literature summary could also be refined as a practical, ready-to-use guide for planning the USG interventions of the lateral elbow in clinical practice.
Keywords: ultrasonography; elbow; tendon; intervention; pain